Nitrogen reduction with green manure roots return maintains spring wheat yield and alleviates soil N2O emission in saline-alkali agroecosystem - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Hanjiang Liu; Jie Zhou; Yuyi Li (Resources, Environment and Sustainability)
The growing global demand for grain drives a greater need for nitrogen (N) input. Yet, it contributes to nitrous oxide (N2O) emissions, aggravating global climate change. To tackle this dual challenge of fulfilling crop demands while maintaining or reducing N2O emissions, a field study was performed in wheat-green manure cropping system to assess the effects of varying fertilizer application (N100, N90 and N80: N fertilizer reduced by 0%, 10% and 20%) combined with green manure return strategy (GMR: green manure roots return, GMRS: green manure roots and shoots return), and wheat fallow after harvest (CK) on wheat yield and yield stability from 2020 to 2024, N2O emissions, as well as N2O emission intensity from 2022 to 2024. Results showed that, although N fertilizer combined with green manure return strategy increased spring wheat yield by 8%–22% by increasing soil mineral N contents, it decreased yield stability compared with CK. Soil N2O emissions were mainly negatively and positively regulated by pH and NO3−-N content in saline-alkali soil, respectively. N80 decreased cumulative soil N2O emission and N2O intensity by 20% and 10% compared with N100, respectively. Irrespective of the variations in N fertilizer levels, GMR decreased cumulative N2O emission and N2O intensity by 20%–34% and 22%–38% compared with GMRS, respectively. Overall, the findings highlighted N fertilizer reduced by 20% (160 kg N ha −1) with green manure roots returned in relative to normal rate (200 kg N ha −1) is a viable option to ensure spring wheat yield and alleviate soil N2O emission in saline-alkali agroecosystem.